ANALISIS KEMAMPUAN BERPIKIR LOGIS PADA MATERI PELUANG DI KELAS IX SMP NEGERI 1 TAKENGON - Noviani, Julia; Hakim, Hilda; Jarwandi, Jarwandi (Program Studi Pendidikan Matematika FTIK IAIN Langsa, 2020)
This study aims to describe the ability of students to think logically on probability subject in class IX in SMP Negeri 1 Takengon. This study uses a qualitative approach to the type of descriptive research. The subject of this study consisted of three students, with the criteria of one student with high ability, one with moderate ability, and one with low ability. Data collection used tests and semi-structured interviews. The instrument used was a test of probabality material. The process of data analysis in this study includes data reduction, data presentation, and drawing conclusions. Based on the analysis of the description of students logical thinking abilities with high criteria (student 1) showed excellent logical thinking skills. Then students with moderate abilities (student 2) showed good logical thinking skills. Student 2 has a deficiency in the stage of thought twitching. While students with low criteria (student 3) demonstrate sufficient logical thinking skills. Student 3 has a deficiency in the stage of thought twitching and drawing conclusions that indicate the student's inaccuracy. Overall the ability to think logically these three students can be said to be good. This can be seen from every work and interview results,, students are able to do most of the indicators of logical thinking ability.